The Effect of Food Control Program for Chronic Kidney Disease Patients at CKD Clinic, Phra Nakhon Si Ayutthaya Hospital - ปานเพียรกุลภัค พิมพ์สุภัค (Journal of Preventive Medicine Association of Thailand, 2018)
This quasi-experimental research was aimed to study the effect of food control program for chronic kidney disease patients at CKD clinic, Phra Nakhon Si Ayutthaya Hospital by applying the theories of self-efficacy. The samples were composed of 33 chronic kidney disease patients that were treated at CKD clinic, Phra Nakhon Si Ayutthaya Hospital. All participants completed the activity in 3 times. The questionnaires of characteristics, perceived self-efficacy in food control, and outcome expectations of food control and food control behavior were used for collecting data. Data were analyzed by using descriptive statistics and Paired t-test. The research showed the most of the sample were male 51.5%, age 61-70 years old 45.5%, averageage 67.42 years, highest education level at primary school level 81.1%, no occupation 81.1%, average monthly income of less than 1,000 Baht 69.7%. Health status: most of the sample have hypertension 42.4% and stage 4 chronic kidney disease 63.6%. The research results revealed that after the intervention, the experimental group was significantly higher perceived self-efficacy in food control, outcome expectations of food control and food control behavior than before the intervention (p<0.001). After the intervention, the experimental group was no difference in Cr and eGFR before the intervention. In conclusion, food control program for chronic kidney disease patients at CKD clinic, Phra Nakhon Si Ayutthaya Hospital was found to be effective in changing perceived self-efficacy in food control, outcome expectations of food control and food control behavior. As a result, the Cr and eGFR unchanged. This intervention should be continued and expanded in another community. The application to fit the context of each community.